Jogos de entretenimento no ciclo educacional básico: critérios de aplicação e desenvolvimento de competências e habilidades - Sanches, Murilo Henrique Barbosa (2019)
The present study aimed to analyze the selection criteria and mechanisms related to the choice of entertainment games applied to basic education as complementary tools for pedagogical work, within the context of intentionality and teaching-learning objectives. This dissertation seeks to answer how to identify the clearest and most efficient criteria related to the choice of an entertainment game according to the disciplinary curriculum and the teaching intention. We also sought to answer how to make this identification by making the selection criteria clear so that other educators could replicate them. This research becomes relevant insofar as it is still unclear why entertainment games are not chosen to compose pedagogical activities and the ways in which experiences are guided. To propose alternatives capable of changing this context, the present study sought to develop a framework that would allow the analysis of these games, offering results indicative of the possibility of using these tools for pedagogical purposes. Thus, we sought to understand the mechanisms necessary for the development of this framework, in order to highlight possible curricular competences associated with entertainment games, as well as the ability of these tools to develop 21st century skills and considering the school context. After the development of this conceptual framework and the analysis of different games by the tool, the one that presented the best performance was applied in the classroom, allowing the analysis of experience results and discussions related to the process efficiency